Deep-sky companions the secret deep - O'Meara, Stephen James, 1956- (Cambridge University Press, 2011)
"In this fresh list, Stephen James O'Meara presents 109 new objects for stargazers to observe. The Secret Deep list contains many exceptional objects, including a planetary nebula whose last thermal pulse produced a circumstellar shell similar to the one expected in the final days of our Sun's life; a piece of the only supernova remnant known visible to the unaided eye; the flattest galaxy known; the largest edge-on galaxy in the heavens; the brightest quasar; and the companion star to one of the first black hole candidates ever discovered. Each object is accompanied by beautiful photographs and sketches, original finder charts, visual histories and up-to-date astrophysical information to enrich the observing experience. Featuring galaxies, clusters and nebulae not covered in other Deep-Sky Companions books, this is a wonderful addition to the series and an essential guide for any deep-sky observer"--